Zebrafish fin and heart: what's special about regeneration?. (October 2016) - Sehring, Ivonne M.; Jahn, Christopher; Weidinger, Gilbert
Abstract : Many organs regenerate well in adult zebrafish, but most research has been directed toward fin and heart regeneration. Cells have been found to remain generally lineage-restricted during regeneration, and proliferative regenerative progenitors can be formed by dedifferentiation from differentiated cells. Recent studies begin to shed light on the molecular underpinnings of differences between development and regeneration. Retinoic acid, BMP and NF-κB signaling are emerging as regulators of cellular dedifferentiation. Reactive oxygen species promote regeneration, and the dynamics of ROS signaling might help explain differences between wound healing and regeneration. Finally, the heart has been added to those organs that require a nerve supply to regenerate, and a trade-off between regeneration and tumor suppression has been proposed to help explain why mammals regenerate poorly.